Kandungan Hara Tanah dan Tanaman Kelapa Sawit Menghasilkan Terhadap Pemberian Tandan Kosong Kelapa Sawit (TKKS) dan Kedalaman Biopori - M. Amin; Chairani Hanum; Charloq Charloq (Universitas Sumatera Utara, 2015)
Research aim to of this was to study effect of aplication empty palm oil fruit bunches (EPOFB)and depth biopori treatment on soil and oil palm nutrient content. The research was conducted inPTPN III Kebun Bangun since July- October 2013, used factorial randomized block design with 2factors and 3 replication. The first factor was aplication EPOFB with levels 0, 16, 32 and 48 kg.The second factor was depth biopori with 50, 75 and 100 cm. The results showed that the highestlevel of N-leaf obtained at a depth of 75 cm with biopori without giving EPOFB, the highest levelof N-soil acquired in treatment without giving EPOFB at depth of 50 and 75 cm, the highest palmleaf chlorophyll obtained at aplication 16 kg EPOFB at depth of 50 cm bioporiKeywords: Palm oil , empty palm oil fruit bunches (EPOFB), biopori